KARAKTERISASI MINERAL DAN GEOKIMIA TAILING TAMBANG TIMAH PULAU BANGKA BAGIAN UTARA - Delita Ega Andini; Fajar Indah Puspita Sari (Geosapta, 2020)
Tailings in this study are the result of Jigs washing in the mining process. This 'mining waste' interesting to study because there is no information that explains the relationship between mineral content and geochemistry so that it has not been widely used. The method used to determine the mineral and geochemical characteristics of tailings is X-ray spectroscopy using XRD and XRF. The mineral found in the tin mine tailings on northern Bangka Island (Pemali, Jebus, Tempilang, and Mapur) is quartz and kaolinite. The trace element shows main Rare Earth Elements (REE) Ce, La, Nd, Sm, Ta, and Y with various concentrations. Radioactive elements are found: Uranium and Yttrium. They are thought to originate from type I granite rocks with acid-to-moderate magma-forming compositions. The affinity of magma forming granite tailings studied was High K Calc Alkaline and Calc-Alkaline. This explains the presence of REE and the radioactive elements in tailings even though they are not present in carrier minerals such as monazite and xenotime.